Pemetaan Hidrogeologi untuk Analisis Zona Konservasi Air Tanah di Cekungan Air Tanah (CAT) Sumowono, Provinsi Jawa Tengah - Putranto, Thomas Triadi; Susanto, Novie; Pangestuti, Dina Rahayuning; Pranata, Mathias Andika Setya (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Groundwater management at groundwater basins Sumowono needs to be done because of the increasing development of the area. This research is oriented to analyzing groundwater conditions, compiling groundwater conservation zones, and explaining conservation zones' suitability with spatial maps. The method used is mapping hydrogeological conditions such as surface observation of rock types, inventory of hydrogeological points of interest, knowing the patterns and directions of groundwater flow, groundwater utilization, and groundwater sampling to measure the degree of acidity and electrical conductivity. From the mapping results, it is found that the lithology is composed of tuffaceous sandstones and volcanic breccias. Based on the free groundwater table analysis, the free groundwater flow pattern follows the topographic slope, flowing from the high topography on the south and southeast sides to the low topography on the north side of the area. The utilization of groundwater is used for irrigation, domestic and fishery purposes. Measurement of groundwater samples' quality for the degree of acidity is between 5.32-7.98 while the electrical conductivity is between 36-550 ÂµS / cm, and the level of damage due to groundwater utilization is included in the safe zone. The groundwater conservation zone consists of recharge areas and spring protection zones. The result of overlapping between the groundwater conservation zone and the spatial plan map shows suitability as a protection zone.